2014
DOI: 10.1186/1546-0096-12-41
|View full text |Cite
|
Sign up to set email alerts
|

MEFV gene mutations in Egyptian children with Henoch-Schonlein purpura

Abstract: BackgroundDue to an increased frequency of vasculitis in FMF patients, many investigators have studied MEFV mutations in patients with HSP. The aim of the study is to investigate the frequency and clinical significance of MEFV mutations in Egyptian children with Henoch-Schonlein purpura (HSP). Investigating MEFV mutations in controls may help in estimating the prevalence of MEFV mutation carrier rate in Egyptian children.MethodsThe study enrolled 90 individuals, sixty children with Henoch-Schonlein purpura (HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
3
11
0
2
Order By: Relevance
“…FMF has been reported more frequently in patients who had HSP than in the general population. MEFV mutations may be related to HSP susceptibility in children [ 24 ]. Salah et al found heterozygous mutations of V726A and E148Q to be the most common in children who also had HSP [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…FMF has been reported more frequently in patients who had HSP than in the general population. MEFV mutations may be related to HSP susceptibility in children [ 24 ]. Salah et al found heterozygous mutations of V726A and E148Q to be the most common in children who also had HSP [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory regulation does not occur correctly in mutated condition. More than 342 sequence variants have already been identified on MEFV gene [47].…”
Section: Introductionmentioning
confidence: 99%
“…[10,14] ve E148Q olarak en sık görülen mutasyonlar değişmektedir. [17,18] Çalışmamızda Ailevi Akdeniz Ateşi tanısı alan 15 hastada en sık gözlenen Ailevi Akdeniz Ateşi mutasyonu M694V idi.…”
Section: Yöntemunclassified
“…En önemli klinik tanısal özellikleri nontrombositopenik purpura, artrit, karın ağrısı, böbrek tutulumudur. [1] Etiyolojisi tam olarak aydınlatılamamakla birlikte, sıklıkla üst solunum yolu enfeksiyonları sonrası immünglobülin A içeren immün komplekslerin damar duvarında birikmesi sonucunda hastalığın ortaya çıktığı ve insidansının 100000'de [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] olduğu bildirilmektedir. [2][3][4][5] Genellikle kendini sınırlayıcı bir süreç olarak tanımlansa da gastrointestinal ve renal tutulum başta olmak üzere organ tutulumları hayatı tehdit edecek düzeyde olabilmekte, özellikle renal tutulum, uzun dönem prognozu belirleyici olmaktadır.…”
Section: Introductionunclassified